Analysis of the integrated role of the Yangtze River Delta based on the industrial economic resilience of cities during COVID-19 - Cai Jia; Zini Cao; Jinkang Hu; Xudong Wang; Long Zhao; Junjun Zhi; Wangbing Liu; Gaohua Zhang; Shilong Ding; Yan Li; Luzhou Lin (Scientific Reports)
Abstract The enhancement of regional comprehensive development ability is significantly impacted by the study on the implementation effect of regional integration strategies. The integration strategy’s impact on urban development during COVID-19 in the Yangtze River Delta(YRD) is unclear. According to prior industrial transfer theory, Hefei, Anhui’s capital, is difficult to transfer industries, and other YRD cities push industry integration in Anhui. This study employs the theory of economic and land resource use to examine the resilience of the industrial economy during an epidemic by using industrial land as a representation of industrial economic development. The three cities in Anhui—Wuhu, Maanshan, and Chuzhou (Wu-ma-Chu) were selected as the research area. The study employed the UNet deep learning method to detect the land use types in Wu-ma-Chu. The land transfer matrix and the standard deviation ellipse were utilised to research the alterations in industrial land use and the spatial distribution of industrial output value, respectively. The results showed that the industrial land in Machu continued to grow during the outbreak, highlighting the resilience of the region’s industrial economy. During 2019–2022, the elliptical ring of industrial output value is distributed in Nanjing, revealing the radiating role of Nanjing in integrating into the integration of the YRD. This confirms China’s YRD integration strategy, strengthens regional economic resilience, and encourages coordinated regional economic development.